Determination of Lead in Saudi Arabian Imported Green Tea by ICP-MS - Ahmed Othman; Seham Al-Ansi; Mohammed Al-Tufail (E-Journal of Chemistry)
Lead (Pb) in nine different Saudi Arabian imported green tea samples originated from China has been determined using inductively coupled plasma mass spectrometry (ICP-MS). Tea infusion and microwave acid digestion procedures are used for sample pre-treatment. The concentrations range of lead (total) in the analyzed green tea samples is 0.231 – 6.340 mg/kg. The total concentration of lead released 3% – 19% into tea infusions with boiling water. The calculated average daily intakes of lead in tea infusions was low and within the bounds of safety (≤0.009 mg/day).